Syeikh Nawawi al-Bantani Thoughts on Bridging Differences Management Fiqh in Indonesia - Rohmatul Uyuni, Yuyun; Nuroh, Nuroh (Universitas Islam Negeri Sumatera Utara, 2025)
The purpose of this study is to analyze the thoughts and contributions of Syeikh Nawawi al-Bantani in bridging the differences in fiqh by identifying the diversity of Mazhab in the Indonesian Muslim community. This research is a literature review or library research using a descriptive qualitative approach and book research or literature study, which is a critical and in-depth review of library materials that are relevant to the study material in this article such as books and scientific articles. The writings and works made by Syeikh Nawawi al-Bantani are studied to explore the differences in jurisprudence that existed in the Indonesian Islamic society at that time. The findings of the study show that Syeikh Nawawi emphasizes a moderate and inclusive approach in dealing with fiqh differences, emphasizing the importance of tolerance and the principle of wasathiyah (moderation). The conclusion of this study states that his thoughts have high relevance in maintaining diversity between Mazhab in Indonesia, and can be the basis for formulating a more constructive fiqh conflict resolution strategy today.